PENGARUH EXCESS AIR TERHADAP CO-FIRING BATU BARA DENGAN BRIKET MSW MENGGUNAKAN INSINERATOR FLUIDIZED BED - Lie, Edgar Reinard; Winaya, I Nyoman Suprapta; Suryawan, I Gede Putu Agus (Teknik Desain Mekanika, 2024)
Abstract One way to reduce pile of Municipal Solid Waste (MSW) is convert it to fuel, one of the example is MSW briquette. Co-fiiring is a method of burning two mixture two different fuel. This research is aim to determine effect of excess air on performance of co-firing combustion on the flue gas and combustion efficiency. Combustion occur in a fluidized bed incinerator consisting of fuel feeder, distributor plate, and a reactor with 1 m height and 0.64 m diameter, the fuel will be fed into the reactor through the fuel feeder located above the reactor then excess air will flowed from the bottom of reactor and heat supplied using a controlled heater via an electric control panel at 800°C . The fuel consist of MSW briquette originating from TPST Kertalanggu, Denpasar and coal with composition 95% of coal and 5% of MSW briquette with a total mass of 140 gram. Variations of excess air that used are variaton 1 (stoichiometric), variation 2 (excess air 10%), variation 3 (excess air 20%), and variation 4 (excess air 30%). The result of this experimental show a better combustion reaction characterized by decrease of CO content and incrased CO2 content in flue gas as excess air incrased. The best combustion efficiency occurred at third variation with excess air 20% which is 89% and decrease occurred in fourth variation with excess air 30% which is 82%, it is show that adding too much excess air can reduce the combustin efficiency. Keywords: Co-firing, MSW briquette, fluidized bed, incinerator, Efficiency, Flue Gas